107k views
1 vote
Graph the following function. -|2x-1|+3

User Hanzala
by
4.3k points

2 Answers

6 votes

To graph the function -|2x-1|+3, we will solve for two cases: when 2x-1 ≥ 0 and when 2x-1 < 0. We will then graph each case and find their intersection point.

To graph the function -|2x-1|+3, we will break it down into two cases: when 2x-1 ≥ 0 and when 2x-1 < 0.

Case 1: 2x-1 ≥ 0

In this case, the function simplifies to -|2x-1|+3 = -(2x-1)+3 = -2x+4.

Case 2: 2x-1 < 0

In this case, the function simplifies to -|2x-1|+3 = -(-(2x-1))+3 = 2x-1+3 = 2x+2.

Now we can graph both cases and observe their intersection point to get the complete graph of the function.

The graph is given below:

Graph the following function. -|2x-1|+3-example-1
User BPDESILVA
by
5.0k points
4 votes

Good evening,

Well I think that's what it is supposed to look like.

Graph the following function. -|2x-1|+3-example-1
User Gaoagong
by
4.5k points